Study of Some Apoptotic Protein Expration in Human Mesenchymal Stem Cells During Toxoplasma Gondii Infection: Studi Ekspresi Beberapa Protein Apoptosis pada Sel Punca Mesenkim Manusia Selama Infeksi Toxoplasma Gondii - Jasim, Suhair Sameer; Mohammed, Safa Yassin; Erzayek, Suha Sulaiman; Hussein, Rand Hatem; Jasim, Ridhab Ajeel (Academia Open, 2024)
Background: Toxoplasma gondii (T. gondii) infection is a significant health concern, particularly during pregnancy, as it can lead to fetal harm and birth abnormalities. Specific Background: The role of apoptosis in managing T. gondii infection remains poorly understood, particularly regarding its molecular mechanisms. Knowledge Gap: The impact of T. gondii infection on apoptosis in mesenchymal stem cells (MSCs) derived from human umbilical cords has not been thoroughly studied in existing literature. Aims: This study aimed to investigate the activation of apoptosis and its regulatory mechanisms in human Wharton’s Jelly mesenchymal stem cells (WJ-MSCs) during T. gondii infection. Results: Using non-enzymatic techniques, we isolated T. gondii from infected and aborted phase-specific placentas. Our findings demonstrated a significant increase in the expression of apoptosis-activating genes (CASP2, CASP3, Bak1) in WJ-MSCs following infection, with a marked decrease in cell viability observed within 2 to 4 hours of exposure to the parasite (P≤0.05). Novelty: This study provides novel insights into the relationship between T. gondii infection and apoptosis in WJ-MSCs, highlighting the specific gene expression changes that occur in response to infection. Implications: Research on T. gondii’s apoptotic pathways is crucial for developing therapeutic strategies to mitigate pregnancy-related adverse effects and improve maternal and fetal health outcomes. Highlights: Increased Apoptosis: T. gondii enhances apoptosis in mesenchymal stem cells. Cell Viability Impact: Significant decrease in WJ-MSC viability after infection. Clinical Relevance: Insights can inform strategies to reduce fetal infection risks. Keywords: Toxoplasma gondii, apoptosis, Wharton’s Jelly mesenchymal stem cells, pregnancy, gene expression